Evaluation of acute and subacute oral toxicity induced by ethanol extract of Boletus griseipurpureus Corner in male mice: Blood parameters and histopathological studies - Anussara Kamnate, On-Anong Somsap, Patcharin Singdam, Gornganok Piboonpol, Wanita Pantong (Journal of Applied Pharmaceutical Science, 2024)
Boletus griseipurpureus Corner originated in the southern and northeastern regions of Thailand, including Narathiwat. It is traditionally consumed for its antioxidant, antibacterial, and gastrointestinal disorder treatment properties. However, there is a lack of toxicological safety studies available. This study aimed to investigate the toxicity of the ethanolic extract of B. griseipurpureus in male mice. Acute and subacute toxicity studies were conducted with different dosages of the extract. In the acute study, treated groups received a single oral dose of 2,000 mg/kg. In contrast, in the subacute study, animals received daily doses at various concentrations of 50, 300, and 2,000 mg/kg for 14 days. Throughout the experiments, signs of toxicity and mortality were observed. Blood and histopathological parameters were analyzed. No significant changes in signs or mortality were observed in any group. However, blood analysis revealed elevated levels of aspartate aminotransferase, alanine aminotransferase, and creatinine. Hematological analysis showed decreased hemoglobin and hematocrit levels. Liver histopathology showed mild inflammation, central vein congestion, pyknotic nuclei, and increased lipid droplets. Kidney sections exhibited glomerular congestion and tubular integrity loss. The study suggests an LD50 greater than 2,000 mg/kg, but moderate signs of toxicity were observed in the kidney and liver. Further studies on chronic exposure and active ingredients are needed to ensure long-term safety.
Keywords: Boletus griseipurpureus Corner, acute toxicity, subacute toxicity, histopathology, mice